Digital Activism and Collective Mobilization: A Narrative Review of Social Identity, Group Efficacy, and the SIMCA Framework - Ali, Muhammad Nur (Sinergi International Journal of Psychology, 2025)
Collective action has long been driven by social psychological mechanisms, particularly collective identity and group efficacy. This narrative review examines the interplay of identity, emotion, and structural conditions in predicting participation in collective mobilization. Drawing on empirical findings from multiple cross-national studies, the review integrates qualitative and quantitative insights to understand how emotional catalysts and digital narratives reinforce collective identification. The methodology involved a systematic review of studies indexed in Scopus, Web of Science, and Google Scholar, using key terms such as "collective action," "social identity," and "group efficacy." Inclusion criteria prioritized peer-reviewed journal articles that employed mixed-method approaches to examine protest dynamics, psychological predictors, and digital activism. The findings confirm that strong social identity, group efficacy, and collective emotion (especially anger and hope) serve as principal motivators for collective participation. However, participation is also mediated by internal constraints such as identity misalignment, and external structural barriers such as authoritarianism, resource scarcity, and cultural repression. Digital media has emerged as a crucial enabler, reinforcing group solidarity and mobilization narratives. These insights underline the importance of inclusive, context-sensitive policies and interdisciplinary strategies in overcoming systemic impediments to mobilization. Future studies should address variations across cultural and geopolitical contexts and explore how technological innovation can facilitate equitable collective engagement. Understanding the synergy between psychological and structural determinants is essential for advancing sustainable collective action.